Evaluasi Masker Peel Off Ekstrak Kulit Pisang Cavendish (Musa acuminata L.) dengan Variasi Konsentrasi PVA - Besse Yuliana; Husnul Khotimah Aris; Habiburrahim` (Jurusan Farmasi Poltekkes kemenkes Makassar, 2026)
Cavendish banana peel (Musa acuminata L.) contains antioxidant compounds such as flavonoids and phenolics, which have potential as active ingredients in cosmetic formulations, particularly peel-off masks. This study aimed to evaluate the stability of peel-off gel mask formulations containing Cavendish banana peel extract with varying concentrations of polyvinyl alcohol (PVA). The research was conducted experimentally in the laboratory using three different formulations (PVA 10%, 13%, and 16%). The banana peel extract was obtained through maceration using 70% ethanol, followed by the formulation of gel-based peel-off masks. The formulations were evaluated for organoleptic properties, homogeneity, viscosity, pH, spreadability, drying time, irritation potential, and stability using cycling tests. The results showed that all formulations met the requirements for organoleptic properties and homogeneity and did not cause skin irritation. The formulation containing 13% PVA (F2) demonstrated the most optimal physical stability, with consistent viscosity, ideal spreadability (5.3–5.6 cm), appropriate pH range (5.82–5.75), and drying time within acceptable limits (17.29–18.17 minutes). The F1 formulation had excessive spreadability and lower viscosity, while F3 showed the fastest drying time but less stable pH values. In conclusion, the 13% PVA formulation exhibited the best physical stability for peel-off gel masks containing Cavendish banana peel extract.